Analisa Erosi dan Sedimentasi Di Hilir Kali Acai Guna Mencegah Daya Rusak Air - Deliana Mangisu; Hery Dualembang (Universitas Teuku Umar, 2023)
The characteristics of the watershed (DAS) have an influence on the size of the discharge, erosion, and sediment in a watershed. Erosion is the process of wearing away topsoil by water or wind. The rate of erosion and sedimentation that occurs is often caused and influenced by climate, soil, topography, plants, land use, human activities, river hydraulic characteristics, and cross-sectional characteristics. The purpose of this study is to obtain information on the magnitude of erosion and sedimentation per unit area in the Acai River. The methods used for this research activity are primary and secondary data analysis methods, using the tools of the ArcGis, and Hecras programs and manual observations and measurements in the laboratory to obtain sedimentation values and shear stresses. The results obtained based on the observations and analysis carried out, the erosion rate using the USLE method was 110.90 tons/ha/year, the peak flood discharge was 18.64 m3/s (Q10) which could not be accommodated by the Acai River and the amount of sedimentation per unit area in the study location for the downstream area is 84,564,439 tons/ha